Assessing the effectiveness of digital archiving systems of higher education in Indonesia - Setyawan, Herman (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This study explores factors influencing the effectiveness of digital archiving systems in Indonesian universities, aiming to improve search time, storage, and organization efficiency. Data Collection Method. Using a mixed sequential explanatory approach, data were collected from 168 university archivists through simple random sampling and 20 key informant interviews. Quantitative data were analyzed using one-sample t-tests and PLS-SEM, while qualitative data underwent thematic analysis. Results and Discussion. The results reveal that system design, archivist satisfaction, and self-efficacy significantly impact the effectiveness of digital archiving systems. However, training programs did not show a significant effect. Self-efficacy mediated the relationship between system design and user satisfaction on system effectiveness. Conclusion. The effectiveness of digital archiving in universities is influenced by system design and self-efficacy. Self-efficacy strengthens the impact of system design and user satisfaction, highlighting the importance of both technical and psychological factors in managing digital archives effectively.